CHEDDA syndrome is an underrecognized neurodevelopmental disorder with a highly restricted ATN1 mutation spectrum. Issue 4 (13th July 2021) - Palmer, Elizabeth E.; Whitton, Chloe; Hashem, Mais O.; Clark, Robin D.; Ramanathan, Subhadra; Starr, Lois J.; Velasco, Danita; De Dios, John Karl; Singh, Emily; Cormier‐Daire, Valerie; Chopra, Maya; Rodan, Lance H.; et al.
Abstract: We describe the clinical features of nine unrelated individuals with rare de novo missense or in‐frame deletions/duplications within the "HX motif" of exon 7 of ATN1 . We previously proposed that individuals with such variants should be considered as being affected by the syndromic condition of congenital hypotonia, epilepsy, developmental delay, and digital anomalies (CHEDDA), distinct from dentatorubral‐pallidoluysian atrophy (DRPLA) secondary to expansion variants in exon 5 of ATN1 . We confirm that the universal phenotypic features of CHEDDA are distinctive facial features and global developmental delay. Infantile hypotonia and minor hand and feet differences are common and can present as arthrogryposis. Common comorbidities include severe feeding difficulties, often requiring gastrostomy support, as well as visual and hearing impairments. Epilepsy and congenital malformations of the brain, heart, and genitourinary systems are frequent but not universal. Our study confirms the clinical entity of CHEDDA secondary to a mutational signature restricted to exon 7 of ATN1 . We propose a clinical schedule for assessment upon diagnosis, surveillance, and early intervention including the potential of neuroimaging for prognostication. Abstract :